Comparative Economic Valuation of Mangrove Ecosystems in Conservation and Non-Conservation Zones in North Sulawesi - Langi, Martina A.; Saroinsong, Fabiola Baby; Walangitan, Hengki D; Nurmawan, Wawan (Jurnal Agroekoteknologi Terapan, 2025)
This study aims to compare the Total Economic Value (TEV) of mangrove ecosystems in two locations in North Sulawesi: the conservation area of Bunaken National Park and the non-conservation coastal region of Bitung City. Employing an economic valuation approach based on Malik et al. (2015), TEV was calculated using the components of Direct Use Value (DUV), Indirect Use Value (IUV), and Option Value (OV). Data were collected through household surveys, field observations, and secondary literature. Preliminary estimates show that the annual per-hectare TEV in Bunaken (USD 7,200) is significantly higher than in Bitung (USD 3,615), primarily due to the substantial contribution of ecosystem services (IUV) in protected areas. The findings emphasize the importance of conservation status in maintaining and maximizing the economic benefits of mangrove ecosystems.